Critical Response of High-Rise Buildings With Deformation-Concentration Seismic Control System Under Double and Multi Impulses Representing Pulse-Type and Long-Duration Ground Motions - Kawai, Akira; Maeda, Tatsuhiko; Takewaki, Izuru (Frontiers in Built Environment, 2021)
The critical responses are investigated for a high-rise building with a deformation-concentration seismic control system under double and multi impulses representing pulse-type and long-duration ground motions, respectively. The critical responses were studied for an elastic-plastic multi-degree-of-freedom (MDOF) shear building model under a double impulse and a multi impulse in the previous papers. However, it seems difficult to derive the critical response for a realistic three-dimensional (3-D) nonlinear frame model with a deformation-concentration seismic control system under such double and multi impulses. The criteria on the criticality of the double and multi impulses for the elastic-plastic MDOF shear building model derived in the previous research are extended to this realistic controlled 3-D frame model by regarding the sum of base story shear forces of both main and sub buildings as a key quantity. In the analysis, the concepts of ‘Double Impulse Pushover (DIP)’ and ‘Multi Impulse Pushover (MIP)’ introduced before are used effectively for clarifying the progressive performances for the increasing input level. The analyses of total input energy, frame hysteretic energy and damper dissipation energy are conducted and the criticality of the input derived based on the above-mentioned criteria is investigated in detail.